2017
DOI: 10.1128/jvi.02030-16
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Interaction of Tumor-Derived HD5 Alpha Defensins with Adenoviruses and Implications for Oncolytic Adenovirus Therapy

Abstract: Defensins are small antimicrobial peptides capable of neutralizing human adenovirus (HAdV) in vitro by binding capsid proteins and blocking endosomal escape of virus. In humans, the alpha defensin HD5 is produced by specialized epithelial cells of the gastrointestinal and genito-urinary tracts. Here, we demonstrate, using patient biopsy specimens, that HD5 is also expressed as an active, secreted peptide by epithelial ovarian and lung cancer cells in situ. This finding prompted us to study the role of HD5 in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Elevated serum HD6 levels were found to be associated with gender in IgAN patients. The current findings suggested that HD5 rather than HD6 There were some evidences suggesting that HD5 or HD6 persists in serum with very low concentration [36,38,39]. We also detected serum HD5 by ELISA and found a relatively low level of HD5 in peripheral blood both from IgAN patients and normal controls.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Elevated serum HD6 levels were found to be associated with gender in IgAN patients. The current findings suggested that HD5 rather than HD6 There were some evidences suggesting that HD5 or HD6 persists in serum with very low concentration [36,38,39]. We also detected serum HD5 by ELISA and found a relatively low level of HD5 in peripheral blood both from IgAN patients and normal controls.…”
Section: Discussionsupporting
confidence: 53%
“…Measurement of Serum and Urine Levels of HD5 and HD6. Serum and urine levels of HD5 and HD6 were measured by the human HD5 and HD6 ELISA kit (USCN Life Science, Wuhan, China) according to the manufacturer's instructions [36]. Serum was diluted 1 : 10 in the appropriate buffer and transferred to microtitre plates for incubation procedures.…”
Section: Patients and Normal Control Subjectsmentioning
confidence: 99%
“…This inhibition presents a barrier to effective viral spread and successful oncolytic therapy. However, type 3 Ad has evolved to manufacture a decoy capsid which sequesters HD5 and renders the virus able to escape endosomes ( 62 ). This finding suggests that the mechanism used by this strain of Ad can be mimicked in order to improve efficacy of existing or potential oncolytic Ad therapies.…”
Section: Adenovirusmentioning
confidence: 99%
“…However, an effective cancer treatment strategy also needs a safe delivery vehicle that can express apoptin protein persistently and deliver it effectively. The human adenovirus serotype 5 (Ad5) is one of such vector that has been used widely to treat a variety of tumors ( 13 16 ). In addition, satisfactory curative effects in the treatment of tumors have been demonstrated by a combination of a recombinant Ad5 and cisplatin ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%